Masculine domination and power in Indonesian TV cook shows - Habsari, Sri Kusumo (Elsevier Ltd., 2014)
This article explores the ways in which gender contributes to the production of TV program well-known with the term of gendered television. It examines semiotically how the shows construct the male host to communicate with their assumed female target audiences.The analysis demonstrates how the male presenters negotiate the traditionally feminized position and the stereotypically domestic sphere to construct his masculine identity.It argues that their role as cooks does not undermine their masculine persona.